Anisakid nematode larvae in freshwater fishes in the St. Lawrence River (Québec, Canada) - Catherine Brisson-Bonenfant; Yves Paradis; David J. Marcogliese; Guillaume Côté; Sarah Aubé; Simon Bernatchez; Philippe Brodeur (International Journal for Parasitology: Parasites and Wildlife)
Anisakid nematodes were observed in freshwater and anadromous fishes in the St. Lawrence River, Québec, Canada. Fish were caught at different locations across a 250 km gradient in the St. Lawrence ecosystem covering freshwater and estuarine habitats. Depending on the sampling sites, nematode prevalence ranged from 30% to 58% for sauger (Sander canadensis) and was 43% for Atlantic tomcod (Microgadus tomcod). For walleye (Sander vitreus), parasites were found only in a fluvial Lake (Lake Saint-Pierre) of the St. Lawrence River, with a prevalence of 23%. In all sampling sites, mean abundance of nematodes in the flesh was higher in sauger than in walleye. Presence of nematodes was significantly correlated with fish total length for walleye, sauger and Atlantic tomcod. Sealworm, Phocanema decipiens s.s., and whaleworm, Anisakis simplex s.s., were found and identified by molecular analysis in sauger and walleye in a fluvial lake (Lake Saint-Pierre), the fluvial estuary and the upper estuary of the St. Lawrence River, while Atlantic tomcod were found infected in a freshwater river tributary (Sainte-Anne River) during spawning.This is the first record of Ph. decipiens s.s. in a non-anadromous freshwater fish. The presence of sealworm and whaleworm in walleye and sauger is attributed to their forays into the brackish waters of the fluvial estuary and suggest large scale migrations between the brackish and the fresh waters of the St. Lawrence River.